Avaliação dos fragmentos florestais da bacia hidrográfica do rio Poxim (Sergipe- Brasil) para fins de restauração ecológica - Jesus, Edilma Nunes de (2013)
The forest fragmentation is a larger challenges for planning the restoration of degraded areas, and is necessary to analyze the characteristics of structure and connectivity of the patches, for can to select appropriate techniques to local situations. This study was conducted to assess the conditions related to the structure and connectivity of forest fragments of river basin Poxim (SE) through landscape metrics considering the attributes and the possibilities of implementing restoration techniques degraded areas. For this, an analysis was made of the structure of the fragments by applying metrics program Patch Analyst 5.0 was selected to identify the area, density and size, edge, shape, and isolation core area, with minimal effect simulation of edge in the area (35 meters). Then, aspects of the functional connectivity in the area were investigated by using indexes connectivity program Conefor sensinode 2.2. The information generated by the programs were compared with the field research of possible actions related to land use fragmentation area. The effects of forest fragmentation are evident in the structural pattern of the patches in the study area. Besides, with respect to connectivity, observed very low values, which indicate the need to increase the work of restoration of degraded areas, to improve network connectivity. In the field research, there were numerous anthropogenics activities that extend the effects of fragmentation in the area, confirming with the data generated by the metrics. Was confirmed the relevance of studies of landscape metrics for fragmented areas and to the actions of subsidy restoration of degraded areas. Thus, due to the harmful consequences that fragmentation brings in the environment, reducing it should be one of the goals of the guidelines in the planning of local biodiversity conservation and landscape restoration